Bearing the cross : Martin Luther King, Jr., and the Southern Christian Leadership Conference - Garrow, David J., 1953- (Perennial Classics, 2004)
Publisher's description: Winner of the 1987 Pulitzer Prize for Biography and the Robert F. Kennedy Book Award, this is the most comprehensive book ever written about the life of Dr. Martin Luther King, Jr. Based on more than seven hundred interviews with all of King's surviving associates, as well as with those who opposed him, and enhanced by the author's access to King's personal papers and tens of thousands of pages of FBI documents, this is a towering portrait of a man's metamorphosis into a legend.